Blanco White and the «Unfortunate Spaniards» - Murphy, Martin (Cuadernos de Ilustración y Romanticismo, 2019)
José María Blanco White used his social connections in London for the benefit of less fortunate compatriots, afrancesados as well as liberales, by obtaining subsistence grants for them from the Royal Literary Fund, a charity founded for the relief of writers in need, of which his close friend James Christie was Registrar.